Inhibitory role of excessive NH3 in NH3-SCR on CeWOx at low temperatures. Issue 9 (17th April 2020) - Liu, Kuo; Huo, Yanlong; Yan, Zidi; Shan, Wenpo; He, Hong
Abstract : An inhibitory effect of excessive NH3 on NH3 -SCR on CeWO x at low temperatures was found, and H2 O rendered the inhibitory effect insignificant for standard SCR. Abstract : An inhibitory role of excessive NH3 at low temperatures in the selective catalytic reduction of NO x with NH3 over CeWO x was revealed and studied comprehensively, both in the presence and absence of H2 O. For the first time, an inhibitory effect of NH3 on NO adsorption over CeWO x has been found.